Investigating the Experimental and Correlational Reliability of Dual-Task Measures in the Psychological Refractory Period Paradigm - Danis, Lila K. (My University, 2022)
The Psychological Refractory Period (PRP) paradigm is frequently used to explore human cognition, executive control, and parallel processing in individuals. However, it is also important to explore the individual differences between people. Before this dual-task paradigm can be used to explore individual differences and be compared to different measures of executive control, it must be established that the effects produced are both experimentally and correlationally reliable, meaning they replicate both across sessions and within individuals. This experiment had 85 McMaster University students participate in a two day experiment that collected multiple measures of executive control and included three PRP dual-task sessions. Data from participants were analyzed to investigate the two effects found in this paradigm: the Backward Compatibility Effect (BCE) in Task 1 (T1) and the PRP Effect in Task 2 (T2). Both effects were found to be individually reliable both experimentally and correlationally. The two effects were then correlated to explore the relationship between them, and a significant positive correlation was discovered. Subsequent analyses separated by response compatibility revealed that incompatible response trials were driving the positive correlation between the PRP Effect and BCE, and that the BCE is related to T1 reaction time on incompatible trials only. These findings suggest the BCE in T1 is driven by response interference between the two tasks on incompatible trials, and this effect then propagates to T2 performance. The reliability of these measures has not previously been explored in this way and this thesis is the first to establish these findings. The results of this thesis support using the BCE and PRP Effect for exploring individual differences between people, as reliable measures that can be explored with other tasks of cognitive control and attention to investigate the presence of similar underlying cognitive processes.
Keywords: Psychological Refractory Period (PRP); dual-task processing; backward compatibility effect (BCE); experimental reliability; PRP Effect; correlational reliability; executive control; task interference